The Effectiveness of K3S Psychoeducation on Changes Community Habits in Managing Waste - Aninditya Maria Shaviratri; Andrian Pramadi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Garbage is a biopsychosocial issue faced by most communities in Indonesia. This condition is thought to be caused by the absence of implementing regulations in the community, the lack of awareness and understanding of every member of the community in managing waste. As a result, there is accumulation and burning of waste which triggers further problems such as health problems. This issue has been going on for years, one of which is in the community of residents of RW027, Sumbersari District, Jember Regency. Analyze the causes and provide appropriate interventions to help the community of RW 027 residents in overcoming waste problems. Data was collected using a questionnaire to obtain prevalence related to the level of awareness of waste management and physical complaints arising from burning and/or waste accumulation. Observations and interviews were also carried out with the authorities, waste officials and several residents who were randomly selected to obtain supporting data related to the causes of the problem. The collected data is analyzed using the theory of planned behavior framework. As the researchers suspected, the cause of the waste problem occurred due to the lack of awareness of community members about the waste problem, the lack of knowledge about the impact of poor waste management and the right way to manage waste. A comprehensive psychoeducational intervention entitled K3S Counseling (Health, Awareness and Waste Management) for 15 people from selected community members using the purposive sampling method effectively had an impact on changing waste management behavior. It was shown that there was a change in the level of knowledge (sig 0.00) and attitude (sig 0.00) and behavior which was followed up one week after the counseling.Sampah merupakan isu biopsikososial yang dihadapi mayoritas komunitas di Indonesia. Kondisi ini diduga disebabkan oleh absennya penerapan regulasi di komunitas, minimnya kesadaran dan pemahaman setiap anggota komunitas dalam mengelola sampah. Akibatnya terjadi penumpukan dan pembakaran sampah yang memicu masalah lanjutan seperti masalah kesehatan. Isu ini terjadi bertahun-tahun, salah satunya di komunitas warga RW027 Kecamatan Sumbersari, Kabupaten Jember. Menganalisa penyebab dan memberikan intervensi yang sesuai untuk membantu komunitas warga RW 027 dalam mengatasi masalah sampah. Data dikumpulkan menggunakan kuesioner untuk memperoleh prevalensi terkait tingkat kesadaran pengelolaan sampah dan keluhan fisik yang timbul akibat pembakaran dan/atau penumpukan sampah. Observasi dan wawancara juga dilakukan terhadap pihak otoritas, petugas sampah dan beberapa warga yang terpilih secara acak, untuk mendapatkan data penunjang terkait penyebab masalah. Data yang terkumpul dianalisa menggunakan kerangka berpikir theory planned behaviour. Sesuai dugaan peneliti, penyebab masalah sampah terjadi karena ketiadaan kesadaran anggota komunitas terhadap masalah sampah, minimnya pengetahuan tentang dampak dari buruknya pengelolaan sampah dan cara yang tepat untuk mengelola sampah. Intervensi psikoedukasi komprehensif berjudul Psikoedukasi K3S (Kesehatan, Kesadaran dan Kelola Sampah) terhadap 15 orang dari anggota komunitas terpilih dengan metode purposive sampling secara efektif berdampak pada perubahan perilaku mengelola sampah. Ditunjukkan adanya perubahan pada level pengetahuan (sig 0.00) dan sikap (sig 0.00) dan perilaku yang di tindaklanjuti satu minggu setelah intervensi.